IMPACT OF SERVICE QUALITY ON CUSTOMER SATISFACTION: A STUDY ON SERVQUAL MODEL IN SELECTED PRIVATE SECTOR BANKS OF RAIPUR DIVISION IN CHHATTISGARH (International Journal of Food and Nutritional Sciences, 2022)
This study investigates the impact of service quality on customer satisfaction in the context of private sector banks operating within the Raipur Division of Chhattisgarh. The research employs a mixed-method approach, incorporating both quantitative and qualitative methodologies to gather data. The study aims to assess customers' perceptions of service quality across various dimensions such as Tangibility, Reliability, Responsiveness, Assurance and Empathy, as outlined in the SERVQUAL model. The findings of this research are expected to contribute to the understanding of how service quality dimensions impact customer satisfaction in the banking sector, particularly within the context of Raipur Division in Chhattisgarh. The implications of the study may inform bank management strategies to enhance service quality and ultimately improve overall customer satisfaction, thereby fostering loyalty and competitive advantage in the market